Short- and Long-Term Effects of Within-Session Client Speech on Drinking Outcomes in the COMBINE Study - Houck, Jon M; Manuel, Jennifer K; Moyers, Theresa B (Journal of studies on alcohol and drugs, 2018)
There is evidence of a causal chain in motivational interviewing (MI) involving counselor MI-consistent skills, client change language, and outcomes. MI was a key component of the combined behavioral intervention in the Combined Pharmacotherapies and Behavioral Interventions for Alcohol Dependence (COMBINE) Study. Participants in COMBINE were treatment-seeking and medication-seeking, and were required to maintain a period of abstinence before enrollment. Counselors were closely monitored and were temporarily removed from the study for remediation and supervision if their performance fell below threshold. The purpose of this study was to evaluate the MI causal chain among initial-session combined behavioral intervention audio recordings in this unique sample of highly motivated clients and highly monitored counselors. Session 1 audio recordings (N = 254, 73.5% men) were evaluated using the Motivational Interviewing Skill Code Version 2.0 with good interrater reliability. Counselor speech was measured using a summary measure of MI-consistent behavior. Client change language was assessed, using change talk and sustain talk. The outcome measure of drinks per week was computed using the COMBINE data set. Higher sustain talk was significantly associated with increased drinking during treatment, whereas higher change talk was significantly associated with decreased drinking at the 1-year follow-up. In addition, there were significant indirect effects linking counselor behavior, client speech, and drinking both during treatment and at 1 year. Results supported the posited causal chain for MI. Despite somewhat lower variability of counselor behavior and use of a coding instrument that did not capture directional counselor behaviors, counselor behavior, client speech, and drinking outcomes were clearly linked in this unique sample.